Machine Learning-Driven Identification of Synergistic Herbal Formulations for Modulating Neuroinflammation - Luceias Janes; Aarav Joshi; Christopher D. Reed (International Journal of Clinical and Translational Medicine, 2026)
The identification of synergistic herbal formulations for modulating neuroinflammation presents a complex systems challenge that sits at the intersection of machine learning, network pharmacology, and translational medicine. Neuroinflammation is not a single molecular target but an emergent property of multicellular signaling networks involving microglia, astrocytes, neurons, and peripheral immune mediators. Herbal medicines contain numerous phytochemicals that may act across multiple targets, making them conceptually attractive for network-level intervention but difficult to evaluate using conventional reductionist paradigms. This paper examines how machine learning-driven discovery platforms can be designed to identify synergistic herbal combinations while addressing structural trade-offs in data integration, model architecture, validation, governance, and deployment. It situates the problem within the broader context of systems pharmacology and network medicine, emphasizing that data infrastructure choices shape the hypothesis space available to predictive models. The discussion covers heterogeneous knowledge graphs, graph neural networks, community-based approaches, and the challenges of translating computational predictions into reproducible preclinical evidence. Rather than advocating a single algorithmic solution, the paper argues that robust discovery requires a layered architecture in which machine learning serves as an inference engine embedded within a larger socio-technical system. This system must account for botanical variability, algorithmic fairness, regulatory ambiguity, data stewardship, and the equitable distribution of benefits. By foregrounding these structural and governance dimensions, the paper offers a framework for building sustainable and responsible platforms for herbal formulation discovery in neuroinflammatory disease.